Report of The Seminar on Social Welfare in a Developing Economy (22nd to 26th September, 1963 - Planning Commission (Planning Commission, 1963)
It was inaugurated by the Prime Minister, Shri Jawaharlal Nehru. He said in his inaugural address that Social Welfare in its broadest sense was the aim of all development planning. Prof. V. K. R. V. Rao, Member, Planning Commission, addressing the inauguration session, said that industrialisation, urbanisation and growing use of science and technology were the major manifestations of economic development. He emphasised that Social Welfare had a great contribution to make in mitigating the undesirable social consequences of these three features of economic development.
Planning Commission Government of India
Planning Commission Government of India